Genetic diversity and elite gene introgression reveal the japonica rice breeding in northern China - Dan LIU; Jia-yu WANG; Xiao-xue WANG; Xian-li YANG; Jian SUN; Wen-fu CHEN (Journal of Integrative Agriculture, 2015)
Abundant genetic diversity and rational population structure of germplasm benefit crop breeding greatly. To investigate genetic variation among geographically diverse set of japonica germplasm, we analyzed 233 japonica rice cultivars collected from Liaoning, Jilin and Heilongjiang provinces of China, which were released from 1970 to 2011 by using 62 simple sequence repeat (SSR) markers and 8 functional gene tags related to yield. A total of 195 alleles (Na) were detected with an average of 3.61 per locus, indicating a low level of genetic diversity level among all individuals. The genetic diversity of the cultivars from Jilin Province was the highest among the three geographic distribution zones. Moreover, the genetic diversity was increased slightly with the released period of cultivars from 1970 to 2011. The analysis of molecular variance (AMOVA) revealed that genetic differentiation was more diverse within the populations than that among the populations. The neighbor-joining (NJ) tree indicated that cultivar clusters based on geographic distribution represented three independent groups, among which the cluster of cultivars from Heilongjiang is distinctly different to the cluster of cultivars from Liaoning. For the examined functional genes, two or three allelic variations for each were detected, except for IPA1 and GW2, and most of elite genes had been introgressed in modern japonica rice varieties. These results provide a valuable evaluation for genetic backgrounds of current japonica rice and will be used directly for japonica rice breeding in future.